(untitled) (Journal of Hama University, 2021)
the search run out in agricultural season 2020-2019 within aplastic hall covered with poly ethylene for study effect of pruning methods on growth and prodaction grafted tomato. using agriculture hybrid tomato(F1 0097) and the origin Divencer for grafted tomato onto it. The study included four methods(treatment) for form tomatoes grafted on the origin Divenser and every treatment was planted in four repeaters according to the design of complete random sectors. The results showed that grafted tomato on the origin Divencer achives significant increase in vegetative growth from where length of stem(248.4) cm in treatment T2 and area paper flat in comparaison with control(31361.97 )cm2/plant in treatment T4 just as grafted treatment T4 exceeded the number of flowers(96.37)flower/plant and fruiting fruits (78.38) fruit/plant in comparison with control. Tomato pruning methods on four stems achives larger number of flowers and fruiting fruits on the plant and give larger quality of prodaction (15.998) kg/m2 in comparison with control and other pruning methods.